PENGARUH LIKUIDITAS DAN AKTIVITAS TERHADAP PROFITABILITAS PERUSAHAAN WHOLESALE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Catur KUmala Dewi, Ari Wahyu Elfreda Aplonia Lau, (EKONOMIA, 2018)
Profit is the difference in the amount of income compared to the costs incurred by the company. some wholesale firms earn profit from 2013-2017, on the other side followed by an increase or decrease in the amount of current assets, total assets, sales and current liabilities. This research was conducted with the purpose to determine the effect of liquidity (curent ratio) and activity (inventory turn over) on profitability (return on assets). The grand theory used is financial management that focuses on liquidity, activity and profitability. The method used in this research is the Library Research method using secondary data and then collecting the data. Determination of samples using purposive sampling by taking some wholesale firms that always earn profit from 2013 - 2017. The analytical tool used to determine the effect of liquidity and activity on profitability is multiple linear regression analysis. Based on the results of multiple linear regression analysis, it is known that liquidity (current ratio) partially has a significant effect on return on assets because it has a significance the t value is <0.05.Activities (inventory turn over) partially have a significant effect on return on assets because it has a significance the t value is <0.05. The results of multiple linear regression analysis are simultaneously known that liquidity (current ratio) and activity (inventory turn over) simultaneously have a significant effect on return on assets because having a test significance the F value is <0.05. Therefore can be concluded that the first, second and third hypotheses are accepted.